Identification of Bacterial Protein Interaction Partners Points to New Intracellular Functions of Francisella tularensis Glyceraldehyde-3-Phosphate Dehydrogenase - Kopeckova, Monika; Pavkova, Ivona; Link, Marek; Rehulka, Pavel; Stulik, Jiri (Frontiers in Microbiology, 2020)
Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is well known for its involvement in numerous non-metabolic processes inside mammalian cells. Alternative functions of prokaryotic GAPDH are mainly deduced from its extracellular localization and ability to bind to selected host proteins. Data on its participation in intracellular bacterial processes are scarce, as there has been to date only one study dealing with this issue. We previously have reported several points of evidence that the GAPDH homologue of Francisella tularensis, GapA, might also exert additional non-enzymatic functions. Following on from our earlier observations, we decided to identify GapA’s interacting partners within the bacterial proteome and to explore its new roles at intracellular level. The quantitative proteomics approach based on stable isotope labelling of amino acids in cell culture (SILAC) in combination with affinity purification and mass spectrometry enabled us to identify 18 proteins potentially interacting with GapA. Six of those interactions were further confirmed by alternative methods. Half of the identified proteins were involved in non-metabolic processes. Further analysis together with quantitative label-free comparative analysis of proteomes isolated from the wild-type strain and strain with deleted gapA gene suggests that GapA is implicated in DNA repair processes. Absence of GapA promotes secretion of its most potent interaction partner, the hypothetical protein with peptidase propeptide domain (PepSY), thereby indicating that it impacts on subcellular distribution of some proteins.